TOJIKISTON QURUQLIK MOLLYUSKALARI (GASTROPODA, PULMONATA) NI O‘RGANISH NATIJALARI VA KELGUSIDAGI VAZIFALAR - Izzatullayev , Z.I; Pozilov , A (Actual problems and prospects of the study of the fauna, 2024)
For the first time, the fauna of land gastropod (Gastropoda) molluscs of the territory of Tajikistan was studied and its taxonomic composition was compiled. At present, 106 species of molluscs belonging to the pulmonary (Pulmonata) subclass have been identified in this area, and they belong to 36 genera, 15 subgenera, 20 families, and 1 family. From the composition of total molluscs: 13 species - Western Pamir region are recorded as new species for science. Differences between the species composition of the malacofauna of the mountain ranges of Northern and Southern Tajikistan have been identified. Subtropical, tropical species with tropical roots are recommended for thorough study.